Productive and Reproductive Performance of Ewes at 60 and 90 Days Postpartum Treated by Different Weaning System - N. da S. Heimbach; C. C. B. F. Ítavo; L. C. V. Ítavo; A. M. Dias; G. dos S. Difante; F. de A. Borges; A. L. C. Gurgel; K. L. da S. Monteiro; C. O. de O. Frangiotti; T. F. F. de S. Arco; M. C. M. da Costa; M. V. G. Niwa (Tropical Animal Science Journal, 2020)
Based on the assumption that the time required by the lamb to reach a certain weight at slaughter (slaughter weight) is partially dependent on the amount of milk ingested during suckling, and on the dietary management of the sheep and lamb. Our study proposes to examine the effects of the weaning system on the productive and reproductive performance of ewes supplemented with creep-feeding during grazing on Marandu pastures with their lambs and weaned at two different ages (60 and 90 days). Ewes were divided into two treatment groups (weaning ages) according to birth type (single or twin), in two consecutive years. The experimental period was the time from lambing to weaning. Data were evaluated by analysis of variance and means were compared by Tukey’s test at the 0.05 significance level. There was no effect of year of observation on the parameters measured. Ewes did not show any differences in age and weight at lambing, weight at weaning, weight change, or time return to estrus. The average weight loss was 6 kg and the average time to return to estrus was 49 days. The highest averages for weaning weight (23.25 kg) and total weight gain (19.37 kg) of lambs, and lamb weight-to-ewe weight ratio (51.84%) were observed in weaning at 90 days of age. Body condition score and worm egg count per gram of feces of ewes were not affected by the treatments. The reproductive and productive performance of sheep on tropical pastures is not affected by the weaning system. It is recommended to conduct weaning at 90 days to obtain a better performance of lambs.